Processing of Climatological Data for Model Initialization - Peggion, Germana; Foo, Grace (1993)
This document describes and documents a numerical procedure to compile data sets to be applied in the North Atlantic (NA) basin-wide numerical simulations. The specific objectives are: (1) to acquire climatological data sets for the NA and archive them in a data library; (2) to develop an interpolation procedure for 2-D and 3-D data fields from a regular grid into the generalized coordinate system adopted by the ocean models; and (3) to prepare plotting facilities for the display and presentation of the original and interpolated data sets.